2020
DOI: 10.1093/nar/gkaa410
|View full text |Cite
|
Sign up to set email alerts
|

FUS ALS-causative mutations impair FUS autoregulation and splicing factor networks through intron retention

Abstract: Abstract Mutations in the RNA-binding protein FUS cause amyotrophic lateral sclerosis (ALS), a devastating neurodegenerative disease. FUS plays a role in numerous aspects of RNA metabolism, including mRNA splicing. However, the impact of ALS-causative mutations on splicing has not been fully characterized, as most disease models have been based on overexpressing mutant FUS, which will alter RNA processing due to FUS autoregulation. We and others have recently cre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
89
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 78 publications
(99 citation statements)
references
References 81 publications
8
89
2
Order By: Relevance
“…Our results highlight that Taf15, one of the three members of the FET family (along with Fus and Ewsr1), is increased in both Ribo-Fus ∆14/∆14 and Ribo-Fus -/datasets. Moreover, previous findings have shown that mutant FUS impairs its autoregulation leading to an increase in RNA levels (Humphrey et al, 2020); we here find that Fus is increased in the mutant translatome dataset ( Fig. 5D), indicating that impaired autoregulation could indeed alter FUS protein levels.…”
Section: Mutant Fus Impairs Translation Of Fmrp Target Rnas In Vivosupporting
confidence: 77%
See 3 more Smart Citations
“…Our results highlight that Taf15, one of the three members of the FET family (along with Fus and Ewsr1), is increased in both Ribo-Fus ∆14/∆14 and Ribo-Fus -/datasets. Moreover, previous findings have shown that mutant FUS impairs its autoregulation leading to an increase in RNA levels (Humphrey et al, 2020); we here find that Fus is increased in the mutant translatome dataset ( Fig. 5D), indicating that impaired autoregulation could indeed alter FUS protein levels.…”
Section: Mutant Fus Impairs Translation Of Fmrp Target Rnas In Vivosupporting
confidence: 77%
“…Importantly, FUS mutations, as well as loss of FUS, induce alterations in transcript expression, with the latter having a stronger effect (Humphrey et al, 2020). These changes can influence the MN translatome composition, nonetheless we found alterations in our translatome datasets that did not correlate with a change in the total spinal cord RNA (input) expression, both in this dataset, and in our previous high-depth RNA-seq data (Humphrey et al, 2020) ( Supplementary Table 1). Further, as MN-derived transcripts are a minority of the total spinal cord RNA, we set out to understand whether mutant FUS had an additional gain of function on the MN translatome by comparing the effect of mutant FUS expression to that of FUS knockout.…”
Section: Mutant Fus Impairs Translation Of Fmrp Target Rnas In Vivomentioning
confidence: 48%
See 2 more Smart Citations
“…This is particularly relevant for ALS-linked genes, genes encoding for cytoskeletal proteins and, notably, other RBPs [8,9]. Importantly, cellular levels of ALS-linked RBPs are tightly regulated by both auto-regulation mechanisms [10][11][12] and cross-regulatory mechanisms [9,[12][13][14][15][16]. The neural RBP HuD (encoded by the ELAVL4 gene), a novel component of cytoplasmic inclusions in FUS, TDP- 43 and sporadic ALS patients [9,14], represents an example of such cross-regulation.…”
Section: Introductionmentioning
confidence: 99%